Association of interleukin-1 gene polymorphisms with Alzheimer's disease. - Nicoll, J; Mrak, R; Graham, D; Stewart, J; Wilcock, G; MacGowan, S; Esiri, M; Murray, L; Dewar, D; Love, S; Moss, T; Griffin, W (2000)
Interleukin-1 (IL-1) is markedly overexpressed in Alzheimer's disease. We found the IL-1A 2,2 genotype in 12.9% of 232 neuropathologically confirmed Alzheimer's disease patients and 6.6% of 167 controls from four centers in the United Kingdom and United States (odds ratio, 3.0; controlled for age and for ApoE [apolipoprotein E] genotype). Homozygosity for both allele 2 of IL-1A and allele 2 of IL-1B conferred even greater risk (odds ratio, 10.8). IL-1 genotypes may confer risk for Alzheimer's disease through IL-1 overexpression and IL-1-driven neurodegenerative cascades.